From pixels to people - Forecasting and mapping dryland agri-environmental and social changes with earth observation - Fava, Francesco P. (University of Milan, 2025)
Presented at the Jameel Observatory drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 15-16 May 2025